Does School Quality Matter? Evidence from the National Longitudinal Survey of Youth - Betts, Julian R. (The Review of Economics and Statistics, 1995)
The paper searches for links between school quaity and subsequent earnings of students. Using data for white males from the National Longitudinal Survey of Youth, the paper rejects the hypothesis that workers' earnings are independent of which high school they attended. However, traditional measures of school 'quality' such as class size, teachers' salaries and teachers' level of education fail to capture these differences. This result is robust to changes in specification and subsample. The paper contrasts the results with those of D. Card and A. B. Krueger (1992) and speculates that structural changes may have weakened the link between traditional measures of school quality and student outcomes. Copyright 1995 by MIT Press.